Opinion the school functional about the sentences in Kurdish language - Dezay, Abdulwahid; Qader, Hani (Humanities Journal of University of Zakho, 2021)
Fanctionl grammar theory is the strongest is stated as one of the theories of modern language, which pays attention of using and transmitting information. Delivering information is one of the main tasks of this theory. This pathway in language thought is a totally different fundamental of how to use a language in specifying the value of connection of a language with defense of social ability of language and psychic of the speaker and the ways of speaking around. In this investigation another case has been mentioned which is analysing practicable of sentence. In functional view when a speaker expresses a sentence, it should be analysed withen the surrounded people, and the investigation will be about (Grammar, Meaning and society) no sentences should be left and all the sentences should be analysed easily. The investigation willingly gets to the point that thoughtfulness of the sentence must be discussed. According to the pathway, the importance of the investigation focuses on the functional grammar of all the sentences. Ambiguity of the sentences won’t be existed. due to investigation, it is not only about the results. It consists of two parts, the first part is about the school functional theory and the second part is about the principle theory and thoughtfulness fanctionl of the sentence.